MANAJEMEN PEMERINTAHAN KABUPATEN KUANTAN SINGINGI DALAM PENGELOLAAN SAMPAH TAHUN 2018 - Luthfi Dirga Hutri; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research is motivated by the large number of hoarding rubbish around the Capital District and several subdistricts in Kuantan Singingi Regency. The rubbish control in Kuantan Singingi Regency has not been carried out well as evidenced by the non-functioning of several rubbish control sites both TPST or TPS3R. Marginally, the activities in rubbish control are the rubbish accumulation control, the rubbish aggregration, transfer and transportation, processing and final disposal. The rubbish control is grouped into two stages, namely rubbish reduction and rubbish andling with each stage.       The location of this research was carried out at the Kuantan Singingi District Environmental Agency. This research is aimed to describe how the management of rubbish at Kuantan Singingi Regency in 2018. The research method used in this study is a qualitative approach, which in theory the researcher tries to explain the stages activities of government management start from planning, organizing, management programs to coaching and supervision activities carried out by the Kuantan Singingi government especially for environmental agency in rubbish control in 2018 so that it can be seen how the government manage a rubbish matters. Data collection techniques in this study used interview techniques and relevant documentation.               The results of the study were found in the field that government management in rubbish control in 2018 has not been implemented optimally due to several factors. From internal problem of government such as the lack of infrastructure management facilities and the lack of budget. And then from external problem of government such as low levels of community participation in overcoming this problem. so that the management activities carried out by the Kuantan Singingi Regency government cannot be done as well as possible.  Keywords : Planning, Organizing, Program Management, Guidance and Supervision.